Pengembangan Alat Bantu Latihan Shooting Three Point “Portable Knee Touch” Dalam Permainan Bola Basket - Muh Isna Nurdin Wibisana; Difa Arya Saputra; Bertika Kusuma Prastiwi (Universitas Negeri Malang, 2023)
Three point shoot is a three point shot technique. These shots are usually only taken outside the line which is worth three points. At the time of initial observation, the position of the student's knees were too forward which made the body movements when shooting unbalanced and the movements were ineffective so that the ball did not reach the hoop and go in. This is what often happens, a cause of errors that are often not seen by coaches who are too focused on hand movements. therefore the researcher wants to develop a tool for three point shooting practice. The purpose of this research is to develop a shooting practice tool (three point shoot) which is used to help practice shooting techniques in basketball practice. This type of research was conducted using the